The Treatment of Malignant Meningioma with Verotoxin - Salhia, Bodour (Nature Publishing Group, 2002)
Malignant meningiomas (MMs) are aggressive intracranial neoplasms with a 75% 5-year recurrence rate. Verotoxin 1 (VT1) is an Escherichia coli toxin, which has recently been shown to have anti-neoplastic action by targeting the globotriosylceramide (Gb(3)) glycolipid on tumor cells and tumor neovasculature. To investigate the potential use of VT1 as a clinical agent for MM, we initially tested 16 meningiomas for Gb(3) expression. Nine of 11 MMs (82%), but only one of five benign meningiomas (20%), were positive for Gb(3). An orthotopic xenograft model was used to test the efficacy of VT1 treatment for MM. We first demonstrated that Gb(3) was highly expressed by the MM cell line, IOMM-Lee, and that this cell line was highly sensitive to VT1 treatment in vitro. A single intratumoral injection of VT1 significantly improved survival in nude mice harboring intracranial tumours (P<.0001). Factor-eight immunostaining of tumours harvested from VT1-treated animals revealed a marked reduction in the tumour microvascular density. In addition, the tumors of VT1-treated animals displayed increased apoptosis by TUNEL analysis and showed a significant decrease in cell proliferation, as determined by MIB-5 immunostaining. VT1 treatment of MM is effective in our orthotopic xenograft model, and warrants further exploration as a potential treatment for these highly anaplastic and aggressive neoplasms.